Motivações dos discentes do programa de Pós-graduação em Direito da Universidade Federal do Paraná (UFPR) para publicar em periódicos científicos no domínio do Direito - Araújo, Paula Carina de (Perspectivas em Ciência da Informaçao.)
The aim of the article is to know the motivations of students of Program of Post-graduate in Law from Universidade Federal do Paraná (UFPR) to publish in scientific journals. It develops a qualitative and exploratory research and it uses the questionary as a data collection instrument. The population of the research are the students of Program of Post-graduate in Law from UFPR. The article classifies the motivations in four categories: scientific-professional, financial/reward, personal and technological. It shows the academic recognition from intellectual production as the most important motivation for the students. The paper also highlights the low availability of time to research and write as the main difficulty. It indicates the long time to evaluate the articles submitted to scientific journals as a difficulty besides those cited in the research, especially when the journals are classified in the highest levels of Qualis from Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES). It also identifies similarities among the results of this research and others that were conducted in Brazil about motivations to publish in scientific journals.